2022
DOI: 10.1177/07067437211070656
|View full text |Cite
|
Sign up to set email alerts
|

“One Degree of Separation”: A Mixed-Methods Evaluation of Canadian Mental Health Care User and Provider Experiences With Remote Care During COVID-19

Abstract: Objectives The COVID-19 pandemic has contributed to a shift from in-person to remote mental health care. While remote care methods have long existed, their widespread use is unprecedented. There is little research about mental health care user and provider experiences with this transition, and no published studies to date have compared satisfaction between these groups. Methods Canadian mental health care users ( n = 332) and providers ( n = 107) completed an online self-report survey from October 2020 to Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 41 publications
0
23
1
Order By: Relevance
“…This study described specific patients' experiences associated with remote mental health care consultations (both telephone and online video). In comparison to earlier studies addressing the health practitioners' perspective regarding remote care as being satisfactory for approximately 59% of health practitioners [11], our study showed a more tempered acceptance towards remote consultations from a patient perspective. However, several situations were deemed positive, for which remote consultations should remain present, including when being faced with transportation issues of when discussing more practical aspects of care or medication.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…This study described specific patients' experiences associated with remote mental health care consultations (both telephone and online video). In comparison to earlier studies addressing the health practitioners' perspective regarding remote care as being satisfactory for approximately 59% of health practitioners [11], our study showed a more tempered acceptance towards remote consultations from a patient perspective. However, several situations were deemed positive, for which remote consultations should remain present, including when being faced with transportation issues of when discussing more practical aspects of care or medication.…”
Section: Discussioncontrasting
confidence: 83%
“…Other barriers mentioned by health practitioners included changing workflow routines and schedules, a lack of training, privacy considerations, increased provider and staff acceptance, and reimbursement possibilities for health care providers (6,(9)(10). From a health care provider point of view, remote care was deemed satisfactory for quite some respondents (59%), of which the majority indicated being open to the further use of remote care after the pandemic [11]. While remote mental health has been deemed cost-effective (or at least as effective as face-to-face care), studies are generally of poor quality and several barriers of implementation have been noted towards generalizability of findings [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a reliable internet connection and workable technology with which to access a virtual platform, clients and caregivers require a private or safe space in which to conduct their appointments. 25 Additional barriers to virtual care identified by our participants included client reluctance or low motivation to engage in care, low English fluency and poor engagement due to young age or clinical presentation (eg, attention-deficit/hyperactivity disorder). The relatively higher sustained uptake of virtual care for return Partnership appointments over the course of the pandemic may reflect, in part, clinicians’, clients’ and caregivers’ increasing comfort with the technology and evolving individual stages of change in its implementation.…”
Section: Discussionmentioning
confidence: 99%
“…While moving appointments from clinic to home environments by means of virtual care may remove many barriers to access to mental healthcare and support continued engagement with services, it does not ensure accessible care for all and, in some instances, may introduce new barriers to care. In addition to a reliable internet connection and workable technology with which to access a virtual platform, clients and caregivers require a private or safe space in which to conduct their appointments 25. Additional barriers to virtual care identified by our participants included client reluctance or low motivation to engage in care, low English fluency and poor engagement due to young age or clinical presentation (eg, attention-deficit/hyperactivity disorder).…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 20 , 21 Many report that they are likely to access telehealth services in some form in the future. 22 , 23 However, this evidence is primarily drawn from studies utilising survey methodology, a format that is not well-suited to deeper exploration of the experiences and perspectives of those who access services. 22 There are few qualitative investigations of people's perspectives of telehealth that employ interview methodology.…”
Section: Introductionmentioning
confidence: 99%